2011
DOI: 10.1073/pnas.1102571108
|View full text |Cite
|
Sign up to set email alerts
|

Activation-induced cytidine deaminase mediates central tolerance in B cells

Abstract: The Aicda gene product, activation-induced cytidine deaminase (AID), initiates somatic hypermutation, class-switch recombination, and gene conversion of Ig genes by the deamination of deoxycytidine, followed by error-prone mismatch-or base-excision DNA repair. These processes are crucial for the generation of genetically diverse, high affinity antibody and robust humoral immunity, but exact significant genetic damage and promote cell death. In mice, physiologically significant AID expression was thought to be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
124
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 102 publications
(137 citation statements)
references
References 43 publications
(59 reference statements)
13
124
0
Order By: Relevance
“…8B). The levels of autoantibodies in Ung 2/2 mice were similar to those detected in age-and sex-matched Aid 2/2 mice, recently described to have a defect in B cell tolerance (44). This novel phenotype of Ung 2/2 mice suggests some role of UNG in preventing autoimmunity.…”
Section: Ung Is Not Limiting For Csrsupporting
confidence: 52%
See 1 more Smart Citation
“…8B). The levels of autoantibodies in Ung 2/2 mice were similar to those detected in age-and sex-matched Aid 2/2 mice, recently described to have a defect in B cell tolerance (44). This novel phenotype of Ung 2/2 mice suggests some role of UNG in preventing autoimmunity.…”
Section: Ung Is Not Limiting For Csrsupporting
confidence: 52%
“…The molecular or cellular basis for this novel phenotype of UNG deficiency, and whether the C57BL/6 background has any incidence, is unknown. It is suggestive that the presence of circulating autoantibodies in AID-deficient mice and patients was recently found to be a consequence of a defect in B cell tolerance (43,44). The mechanism by which AID contributes to B cell tolerance is unknown, but our results suggest the possibility that UNG can be part of this pathway and warrants further investigation.…”
Section: Discussionmentioning
confidence: 83%
“…17 To explain why MYC breaks occur at WGCW but not at CpG 1 whereas CCND1 breaks can occur at either CpG or WGCW, we propose the following mechanistic and developmental model for IgH translocations ( Figure 1B). CpG breaks are favored at the earliest stages of B-cell development when AID is expressed at very low levels [18][19][20][21][22] because deamination of methylated CpG gives rise to T:G mismatches that are repaired 2500-fold less efficiently than U:G mismatches at nonmethylated cytosines. 1 The T:G mismatches preferentially predispose to chromosome breaks because they persist for much longer than U:G mismatches, even though it is likely that both T:G and U:G lesions arise at very low levels.…”
Section: Resultsmentioning
confidence: 99%
“…17 We hypothesize that the non-CpG breaks in MCL might occur in immature/transitional 1 (T1) stage B cells, where AID is expressed at an intermediate level [18][19][20][21][22] (Figure 1B), presumably in conjunction with receptor editing. [22][23][24] This would explain their preference for WGCW motifs Figures 1 and 2). ʈNon-V(D)J break between JH4 and JH5 (see supplemental Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, Aicda-KO mice and AID-deficient patients as well as asymptomatic AID +/-individuals display an impaired central B cell tolerance, resulting in the production of large numbers of autoreactive B cells that migrate from the bone marrow into the periphery (8,28,32). However, we previously reported that autoreactive clones can be prevented from colonizing the mature naive B cell compartment when Tregs are functional, despite the impaired removal of developing autoreactive immature B cells in the bone marrow (16).…”
Section: Discussionmentioning
confidence: 99%